Antioxidative, antiproliferative and antimicrobial activities of phenolic compounds from three myrcia species - Santos, Catarina dos [UNESP]; Galaverna, Renan S.; Angolini, Celio F. F; Nunes, Vania V. A. [UNESP]; de Almeida, Luiz F. R. [UNESP]; Ruiz, Ana L. T. G.; de Carvalho, João E; Duarte, Regina M. T.; Duarte, Marta C. T; Eberlin, Marcos N (MDPI, 2018)
Myrcia bella Cambess., Myrcia fallax (Rich.) DC. and Myrcia guianensis (Aubl.) DC. (Myrtaceae) are trees found in Brazilian Cerrado. They have been widely used in folk medicine for the treatment of gastrointestinal disorders, hemorrhagic and infectious diseases. Few reports have been found in the literature connecting their phenolic composition and biological activities. In this regard, we have profiled the main phenolic constituents of Myrcia spp. leaves extracts by ESI(−)Q-TOF-MS. The main constituents found were ellagic acid (M. bella), galloyl glucose isomers (M. guianensis) and hexahydroxydiphenic (HHDP) acid derivatives (M. fallax). In addition, quercetin and myricetin derivatives were also found in all Myrcia spp. extracts. The most promising antioxidant activity, measured by 2,2-diphenyl-1-picrylhydrazyl (DPPH) scavenging activity, was found for M. fallax extracts (EC50 8.61 ± 0.22 µg·mL− 1), being slightly less active than quercetin and gallic acid (EC50 2.96 ± 0.17 and 2.03 ± 0.02 µg·mL− 1, respectively). For in vitro antiproliferative activity, M. guianensis showed good activity against leukemia (K562 TGI = 7.45 µg·mL− 1). The best antimicrobial activity was observed for M. bella and M. fallax to Escherichia coli (300 and 250 µg·mL− 1, respectively). In conclusion, the activities found are closely related to the phenolic composition of these plants.
Keywords: Biological activities; ESI(−)Q-TOF-MS; Myrcia spp.; Phenolic compounds